Penerapan Terapi Nafas dalam dan Genggam Jari untuk Nyeri Hernia Lateralis - Idrawati Bahar; M. Fikri Zalius; Netti; Zulfa (Jurnal Kebidanan dan Keperawatan Medika, 2026)
An inguinal hernia is a common hernia that presents as a bulge in the groin or scrotum. Inguinal hernia is a condition of protrusion or weakness of an organ structure. Inguinal hernia is the most common type of hernia, About 25 out of 100 men and 2 out of 100 women suffer from at least one inguinal hernia at some point in their lives.The purpose of this final paper is to apply deep breath relaxation therapy and finger grasping in nursing care to reduce pain intensity in patients for indications of lateral inguinal hernia in the male surgical room of the RSUP. Dr M. Djamil Padang. The research method uses a case report approach. This research was conducted in the male surgical room of the hospital. Dr M. Djamil Padang. The population of all patients in the male surgical room of Dr. M. Djamil Padang Hospital in April-May 2024 as many as 7 people. Sample with purposive sampling technique as many as 2 people. Data collection techniques with interview methods, observation, physical examination and documentation studies. Analysis using pico by comparing the results of nursing care with journals that have been found. The results of the application of finger grip relaxation show that there is a decrease in pain intensity before being given finger grip relaxation, namely a scale of 6 in the first patient and 5 in the second patient, after finger grip relaxation therapy, namely a scale of 2 in the first patient and 2 in the second patient.